Search for bottom-type vectorlike quark pair production in dileptonic and fully hadronic final states in proton-proton collisions at √ =13 TeV - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (Physical Review D, 2024)
A search is described for the production of a pair of bottom-type vectorlike quarks ( VLQs) with mass greater than 1000 GeV. Each VLQ decays into a quark and a Higgs boson, a quark and a boson, or a quark and a boson. This analysis considers both fully hadronic final states and those containing a charged lepton pair from a boson decay. The products of the → boson decay and of the hadronic or boson decays can be resolved as two distinct jets or merged into a single jet, so the final states are classified by the number of reconstructed jets. The analysis uses data corresponding to an integrated luminosity of 138  fb−1 collected in proton-proton collisions at √ =13  TeV with the CMS detector at the LHC from 2016 to 2018. No excess over the expected background is observed. Lower limits are set on the VLQ mass at the 95% confidence level. These depend on the VLQ branching fractions and are 1570 and 1540 GeV for 100% → and 100% →, respectively. In most cases, the mass limits obtained exceed previous limits by at least 100 GeV.